ADMINISTRASI KURIKULUM DALAM MENINGKATKAN KUALITAS PENDIDIKAN ISLAM DI SD IT HIDAYATUL JANNAH SUMATERA UTARA - Aziz, Mursal; Rahmadani, Aulia; Ritonga, Yunizar; Fadillah, Fadillah (Jurnal Manajemen Pendidikan Islam Al-Idarah, 2024)
Curriculum management has an important role, because good curriculum management will make it easier to achieve educational goals optimally. Curriculum implementation is closely related to the term curriculum administration. This research was carried out at SD IT Hidayatul Jannah. The purpose of writing the research is to research the theme of the role of curriculum administration in education at SD IT Hidayatul Jannah. The method used is qualitative research. The subjects of this research are teachers at SD IT Hidayatul Jannah and the data collection techniques that researchers use are interviews, observation and documentation. The results obtained from this research indicate that curriculum administration is very important in improving the quality of education. Among other things, first as a reference in implementing learning. Secondly, curriculum administration plays an important role in organizing and compiling the curriculum in an educational institution. The three curriculum administrations are used as a measure of success and as a tool for improvement.